Efektivitas Program Bantuan Langsung Tunai (BLT) Dana Desa Tahun 2021 di Desa Dangin Puri Kelod pada Masa Pandemi Covid-19 - NGR, Kadek Tassya Millenia Yadnya; Yudartha, I Putu Dharmanu; Winaya, I Ketut (CITIZEN CHARTER, 2023)
As a result of the Covid-19 pandemic, the municipality's economy is in decline and to overcome this, the Indonesian government has announced various measures. This is Village Minister Order PDTT number 11 of November 2019 to prioritize the use of village funds in 2020. Village funds, originally intended for village development and development, were transferred to a cash assistance fund called Village Fund Direct Assistance. The purpose of this study is to determine the success rate of the 2021 Village Fund Direct Cash Assistance Program. The author uses his Sutrisno effectiveness theory as an analytical tool and a qualitative approach using a qualitatively descriptive survey type. The survey site is Dangin Puri Kerod Village in East Denpasar Province. The results of this study suggest that village officials can reach out to potential families of direct cash assistance before they are identified. Keywords: Effectiveness, Direct Cash Assistance, Covid-19